THE SYMBOL OF THE UKRAINIAN NATIONAL COSTUME OF PRECARPATHIA AS A MEANS OF FORMING CULTURAL COMPETENCE OF PUPILS OF SCHOOLS IN MOUNTAINOUS REGION - Klepar, Mariia (Mountain School of Ukrainian Carpaty, 2019)
The Ukrainian national costume of Precarpathia, a symbol of a modern national costume, is considered in the article. Its components as a means of forming the cultural competence of students of mountainous schools. It is emphasized that in modern clothes the features of national, traditional, which makes it more organic, should be shown. The variety and specificity of manufacturing, wearing, colorfulness and brightness of the national costume decoration are characterized. It was emphasized that the national costumes of the population of the Carpathians and the Ukrainian Carpathians have their local features, which are specific to this territory and that each of the ethnographic regions has its own peculiarities and differences.